2021
DOI: 10.51253/pafmj.v71i5.4466
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Concept of Healthy Eating in Relation With Physical Activity and Dietary Habits Among University Students

Abstract: Objective: To evaluate the physical activities and dietary habits and to determine the concept of healthy eating among university students of Pakistan. Study Design: Cross sectional survey. Place and Duration of Study: Three well reputed educational institutes of Lahore Pakistan, from Jul 2019 to May 2020. Methodology: A questionnaire was used for data collection and validated scientifically as well as linguistically by experts. The questionnaire consists of 4 parts demographic and basic prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Alzamil H et al 2019 agreed with the present study and found that; high proportion of the participants consumed breakfast or vegetables 5 days per week, whereas the corresponding proportions for fresh fruit were low adding; proportions of college females who consumed less healthy foods for 3 and more times per day every week were ranging from 21.1% for French fries to 60.4% for chocolates and or candy [8]. The main finding of Hassan et al's study was that university students have unhealthy eating practices [16], Further, Gunes F et al, found that fewer than half of their participants ate the daily recommended amount of fruits and vegetables [17], these findings also were consistent agreed and supported with previous research results on college students from different countries [2,[18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Alzamil H et al 2019 agreed with the present study and found that; high proportion of the participants consumed breakfast or vegetables 5 days per week, whereas the corresponding proportions for fresh fruit were low adding; proportions of college females who consumed less healthy foods for 3 and more times per day every week were ranging from 21.1% for French fries to 60.4% for chocolates and or candy [8]. The main finding of Hassan et al's study was that university students have unhealthy eating practices [16], Further, Gunes F et al, found that fewer than half of their participants ate the daily recommended amount of fruits and vegetables [17], these findings also were consistent agreed and supported with previous research results on college students from different countries [2,[18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 77%
“…Goje et al 2014 presented similar results regarding physical inactivity [26]. Deliens, T et al 2015 supported this result, finding stated that the pattern of physical activity among novice and senior students showed that both groups were physically inactive [27], in addition Alzamil H 2019 reported that most of these female students were physically inactive and had high sedentary behavior [8] and Jayed A et al 2021 added; less physical activity and low eating fitness were factors related with overweight among youthful grown-ups' university students [21].…”
Section: Discussionmentioning
confidence: 58%
“…According to many researchers, implementing educational programs focusing on healthy eating and physical activity can be a key step in building awareness and promoting beneficial health habits among students. Additionally, investing in supporting physical activity by organizing sports activities and providing access to recreational facilities can be an effective incentive for regular exercise [ 55 , 56 , 57 ]. The students, both in our study and the studies conducted by other authors, also noticed negative changes in the quality and quantity of sleep and the level of stress [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%